Pengaruh Kepuasan Kerja Dan Stres Kerja Terhadap Komitmen Organisasi Pada Karyawan UKM Mendunia Centre Kediri - Ratmawati Ratmawati; Edy Suwasono; Heru Sutapa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of job satisfaction (X1) and work stress (X2) on organizational commitment (Y). This study uses quantitative methods with multiple linear regression analysis techniques. The research data were obtained by interview, questionnaire, and observation methods. Sampling in this study used a saturated sampling technique, namely all employees of the UKM Mendunia Center Kediri Foundation as many as 37 people. The results of the study using the SPSS version 25 program assistance show that: (1) job satisfaction partially has a positive and significant effect on organizational commitment with a tcount of 4.749 and a Sig. 0.000 <0.05 (2) and work stress partially has a negative and significant effect on organizational commitment with a tcount of -3.366 and a Sig. value of 0.002 <0.05 (3) job satisfaction and work stress simultaneously have a significant effect on organizational commitment by the Fcount value is 32.284 and the Sig. 0.000 < 0.05. From the results of the multiple linear regression analysis test, it produces the equation Y = 12.597 + 0.355 X1 - 0.193 X2 +e